The long-run impact of bilateral real exchange rate volatility on Malaysia’s bilateral trade balance with its major trading partners / Mazila Md Yusuf - Md Yusuf, Mazila (Universiti Teknologi MARA, Jengka, 2008)
The objective of this paper is to analyse the long-run impact of bilateral real exchange rate volatility on Malaysia’s bilateral trade balance with its major trading partners, comprising the United States, Singapore, Japan, United Kingdom, and Republic of Korea over the monthly period 1990:1 to 2002:12. The long-run impact will be analysed using the cointegration analysis and a vector error correction model (VECM) framework which treats all variables in the model as potentially endogenous. In this study, the GARCH model is employed to measure the bilateral exchange rate volatility. Our findings revealed that there is a positive long-run impact of exchange rate volatility on the trade balance of Malaysia with the United States, a negative long-run impact on the trade balance of Malaysia with Singapore and no impact on the trade balance of Malaysia with the other three countries.